Renting Out Villas in The Villa Kota Bunga by Utilizing Digital Marketing Technology - Suzanna Suzanna (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
Tourism is a field that is directly related to global development and economic growth. Year after year there has been a significant increase in this sector, even though during the Covid-19 pandemic it had experienced a decline, but it is believed by various parties that there will be a period of revival in the tourism sector. In Indonesia, there are many local tourist attractions that are worldwide and many more are loved by both local and foreign visitors. Tourist attractions that are close to the capital city of Jakarta and visited by many tourists include the peak area of Bogor. The main attraction of the peak area is the cool mountain area with tea plantations. Many culinary places, game arenas are offered by local residents. Its location close to the city of Jakarta makes this area always crowded with tourists, especially every weekend. One of the places that is used as a benchmark when on vacation to the top is Villa Kota Bunga Puncak. In Kota Bunga Puncak there are many villa rentals but unfortunately, they are still doing traditional marketing. After observations have been made in the field, the villa marketing is carried out in collaboration with brokers or freelance sales. In general, there is no concept of creating digital marketing content for the rental Villa in Villa Kota Bunga Puncak. From the many rental villas there, in this study we take the example of the case of Villa Wubao. Digital marketing is made possible by a series of adaptive digital touchpoints that include marketing activities, processes, customers or institutions that interact with one another. From existing research, the number of touchpoints is increasing by more than 20% every year as more and more customers using traditional or offline means are switching online or to digital technology. In this research digital marketing strategy will be analyzed and designed based on seven stages: situation analysis, digital marketing strategic planning, objectives (goals), digital marketing strategy, implementation planning, budget, and evaluation plan. Keywords: Digital Marketing, E-Commerce, Tourism, Villa Kota Bunga Abstrak Pariwisata adalah bidang yang berhubungan langsung dengan pembangunan global dan pertumbuhan ekonomi. Tahun demi tahun terjadi peningkatan yang signifikan pada sektor ini, meskipun pada masa pandemi Covid-19 sempat mengalami penurunan, namun diyakini oleh berbagai pihak akan ada masa kebangkitan kembali pada sektor pariwisata. Di Indonesia sendiri terdapat banyak sekali tempat wisata lokal yang sudah mendunia dan banyak lagi disukai oleh para pengunjung baik lokal maupun mancanegara. Tempat wisata yang dekat dengan Ibu Kota Jakarta dan banyak dikunjungi wisatawan antara lain kawasan puncak Bogor. Daya tarik utama kawasan puncak adalah kawasan pegunungan yang sejuk dengan perkebunan teh. Banyak tempat kuliner, arena permainan ditawarkan warga setempat. Lokasinya yang dekat dengan kota Jakarta membuat kawasan ini selalu ramai dikunjungi wisatawan, terutama setiap akhir pekan. Salah satu tempat yang dijadikan patokan saat berlibur ke puncak adalah Villa Kota Bunga Puncak. Di Kota Bunga Puncak terdapat banyak persewaan villa namun sayangnya pemasarannya masih tradisional. Setelah dilakukan observasi di lapangan, pemasaran villa dilakukan bekerjasama dengan calo atau sales freelance. Secara umum belum ada konsep pembuatan konten digital marketing untuk penyewaan di Villa Kota Bunga Puncak. Dari sekian banyak penyewaan villa yang ada, dalam penelitian ini kami mengambil contoh kasus Villa Wubao. Pemasaran digital dimungkinkan oleh serangkaian titik kontak digital adaptif yang mencakup aktivitas pemasaran, proses, pelanggan, atau institusi yang berinteraksi satu sama lain. Dari penelitian yang ada, jumlah titik sentuh meningkat lebih dari 20% setiap tahun karena semakin banyak pelanggan yang menggunakan cara tradisional atau offline beralih ke teknologi online atau digital. Dalam penelitian ini strategi pemasaran digital akan dianalisis dan dirancang berdasarkan tujuh tahapan yaitu analisis situasi, perencanaan strategis pemasaran digital, tujuan (goal), strategi pemasaran digital, perencanaan implementasi, anggaran, dan rencana evaluasi. Kata kunci: Pemasaran Digital, E-Commerce, Pariwisata, Villa Kota Bunga